Pengaruh Kualitas Informasi dan Responsivitas Layanan terhadap Kepuasan Publik pada Kanal Pengaduan Digital Bank Sumsel Babel: Perspektif E-Government - Nasywa Fitri Adelia; Annada Nasyaya (Faculty of Social and Political Science, 2026)
responsiveness on public satisfaction with the digital complaint channel of Bank Sumsel Babel from an e-government perspective. A quantitative approach was employed using an explanatory survey method. Data were collected from 104 respondents who had previously utilized the bank’s digital complaint channel and were analyzed through multiple linear regression using SPSS version 30. The findings reveal that information quality has a positive and significant effect on public satisfaction (t = 21.126; Sig. < 0.001). Similarly, service responsiveness also demonstrates a positive and significant influence on public satisfaction (t = 23.549; Sig. < 0.001). Simultaneously, both variables significantly affect public satisfaction (F = 390.889; Sig. < 0.001). The coefficient of determination (R Square) of 0.886 indicates that 88.6% of the variance in public satisfaction can be explained by information quality and service responsiveness, while the remaining 11.4% is attributed to other variables beyond the scope of this study. These findings underscore the importance of enhancing information quality and service responsiveness to support the effectiveness of e-government implementation and improve public satisfaction with digital complaint services